An Assessment of Socio-economic Status and Occupational Health Hazards of Female Workers in Brick Industries at Western Maharashtra, India - Kharake, Ashali; Deshmukh, Pragati; Pathare, Jyoti; Unde, Maya (Advances in Social Sciences Research Journal, 2025)
The objective of current research work is to assess the socio-economic scenario of the female brick workers and occupational health hazards of the brick industries located in the Pravara River basin from western Maharashtra, India. The entire study is based on primary data which has been collected from extensive field survey through standard questionnaire in the period of October 2022 to May 2023. Total 112 FBW of 14 sites and 8 female brick workers from each site have been selected along Pravara River based on random purposive sampling. The Kessler Psychological Distress Scale (K10) has been implemented to measure the current psychological level of FBW. The paired t-test and McNemer’s analysis have been used for examine sleep duration and sleep quality on and off shift days. The 3 points Likert Scale has been used to examine the occupational health hazards and health problems of FBW. Descriptive statistics were used to summarize and tabulate the data. The socio-economic condition of the FBW indicated that 96% of FBW live in extremely poor condition, 86.61% FBW lives in kutcha house, 78.57% FBW earn about ₹1500/month which is very low income and 69.64% FBW are illiterate. No school and crèche provision for children has been provided by brick owner or local government. The leading causes of occupational hazards were fall from height, stuck by objects, slippage and snake and insect bite as well as after join brick occupation majority of FBW experienced respiratory, skin, eye and gastrointestinal problems. 92.86% of FBW spend long hours (> 12 h) to acquire higher wages. FBW reported longer sleep duration (6.5 ± 0.62 h vs 7.8 ± 0.74 h and p<0.001) and sleep quality (83.92% vs 18.75%) during off-shift day than on-shift day which were linked to moderate psychological distress (33.93%). The study concluded that sustainable approach should be taken to improve the socio-economic condition of FBW and to minimize occupational health hazard in the brick kilns.